Features of structural, energy, electrokinetic and magnetic characteristics of Ti1-xScxCoSb thermoelectric material - Romaka, V.A.; Stadnyk, Yu.V.; Romaka, L.P.; Krayovskyy, V.Ya.; Romaka, V.V.; Horyn, A.M.; Konyk, M.B.; Romaniv, I.M.; Rokomanuk, M.V. (Journal of Thermoelectricity, 2019)
The crystalline and electronic structures, electrokinetic, energy and magnetic characteristics of the Ti1-xScxCoSb thermoelectric material were investigated in the ranges T=80–400 K, x=0.005–0.15. Mechanisms of simultaneous generation of structural defects of the acceptor and donor nature were established. It was shown that the structure of TiCoSb basic compound is defective, comprising defects of the donor and acceptor nature as a result of location in the tetrahedral voids of additional Co* atoms and the presence of vacancies at the 4a position of Ti atoms. The introduction of impurity Sc atoms into TiCoSb compound by substitution at the 4a position of Ti atoms generates the acceptor defects, and the ratio of concentrations of available donors and generated acceptors determines the position of the Fermi level εF, type, and the mechanisms of conduction for Ti1-xScxCoSb. Bibl. 12, Fig. 8.